OPTIMIZING MSME COMPETITIVENESS IN THE DIGITAL ERA THROUGH INNOVATION CAPABILITY, AND CUSTOMER RELATIONSHIP MANAGEMENT - Deandra Vidyanata; Melvin Krisdiana Djami Rane; Ita Musfirowati Hanika; Nani Nani (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
The main aim of this research is to analyze the influence of innovation capability and customer relationship management on MSME competitiveness. This research uses a literature and field research design with a causal associative approach. This study uses a research instrument test consisting of validity and reliability tests. The quantitative analysis consists of a normality test, regression test, hypothesis test, correlation test, and coefficient of determination. The research results conclude that innovation capability and customer relationship management have a positive and significant effect on MSME competitiveness. The implications of this research state that the ability to create innovative products or services can differentiate a company from its competitors in the market. Innovation allows companies to offer something unique and added value to customers. With a deeper understanding of CRM, MSMEs can identify new opportunities, optimize marketing strategies, and increase customer retention to improve MSME performance, growth and sustainability in an increasingly competitive business environment.